1981
DOI: 10.1159/000182327
|View full text |Cite
|
Sign up to set email alerts
|

Neoplasia after Successful Renal Transplantation

Abstract: Neoplasia developed in 14 of the first 193 patients to receive renal transplants at the Johannesburg Hospital. No case of reticulum cell sarcoma was diagnosed and an extremely high incidence of squamous carcinoma of the skin occurred. Of the latter patients, 62.5% originally suffered from analgesic nephropathy, suggesting a possible relationship between the two conditions. Transplant recipients who later developed tumours were less likely to experience rejection episodes than other recipients, and this may sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…No correlation could be observed between cutane ous lesions and such parameters as diabetes, daily or alter nate-day steroid regimen, number of rejection episodes, the use of antilymphocyte globulin or plasma creatinine levels. This agrees with the data of Disler et al [10], which were only concerned with the development of neoplastic manifestations.…”
Section: Miscellaneoussupporting
confidence: 93%
“…No correlation could be observed between cutane ous lesions and such parameters as diabetes, daily or alter nate-day steroid regimen, number of rejection episodes, the use of antilymphocyte globulin or plasma creatinine levels. This agrees with the data of Disler et al [10], which were only concerned with the development of neoplastic manifestations.…”
Section: Miscellaneoussupporting
confidence: 93%
“…The studies that followed focused on either cutaneous malignancies or PTLD. In 1981 Disler et al 14 showed that transplant recipients with cutaneous SCC had a greater risk of developing metastatic disease compared with the general population. Five years later, a study reported by Gupta et al 9 revealed that 74% of cutaneous SCC and BCC in the renal transplant population presented on the face, head, and neck.…”
Section: Discussionmentioning
confidence: 99%
“…Transplant patients with malignancy were found to have fewer rejection crises and better transplant longevity. This finding suggests that longer graft life may be associated with a greater degree of immunosuppression, which in turn is associated with diminished antitumor surveillance, and thus increased tumor growth ,…”
Section: Commentmentioning
confidence: 99%